Advancing Sustainable Development Goals (SDGs) by 2036: Strengthening Policy, Driving Innovations, and Global Partnerships for a Sustainable Future - Nodangala , Zibele N.; Thukuse, Bulelani (Eastasouth Institute, 2025)
This paper examines the achievements and progress made in implementing sustainable development principles aimed at improving people's quality of life. It further highlights the pivotal roles of policy reform, innovation, and global partnerships in advancing a more environmentally sustainable and socially equitable future. Amid global challenges like climate change, inequality, and resource depletion, the SDGs provide a strategic framework for inclusive and transformative development. This study critically examines the progress made toward these global goals by evaluating the effectiveness of policy frameworks and technological innovations within selected institutions in South Africa, allowing for a comparative analysis of their roles in fostering sustainable economic, social, and environmental development. By analysing case studies from South Africa and Germany and drawing on international cooperation frameworks such as the UN SDG Partnerships Platform, this paper investigates how governments, businesses, and civil society can collaborate to accelerate the implementation of the Sustainable Development Goals (SDGs). This study places special emphasis on how renewable energy, sustainable agriculture, climate action, and social equity collectively contribute to fostering inclusive and equitable economic growth. Furthermore, the paper reviews emerging challenges such as the impacts of technological disruption, geopolitical conflicts, and rising inequalities, and proposes strategies for addressing these obstacles. Through a detailed review of global initiatives, regulatory mechanisms, and innovations driving sustainability, this study aims to contribute to the ongoing discourse on how to build a more resilient, equitable, and environmentally sustainable world by 2036.